Comportamento eleitoral e instituições políticas na América Latina - Mariela Campos Rocha (2018)
This dissertation aims to discuss the changes in the electoral behavior of the Latin-Americans in presidential elections, and how higher or lower stability of the political party system and the institutional design of the electoral system result in earnings in the fomentation of identification with a party and with the voting for a party. Many studies bring explanations for the identification with a party, but herein it will be considered the consistency of this identification in the voting, through a variable that was called "partisan vote". Therefore, we propose to think about what effect the institutions of the party system and electoral system have on the occurrence of the partisan vote in Latin-American countries. The empirical analysis was developed using multivariate tests, in hierarchical quantitative models, being the main sources of data the official electoral results, using as sources the websites of official bodies that organize the national elections in each country; the research data from the Parliamentary Elites in Latin America (PELA), and from the Americas Barometer (LAPOP) for 2014 in 17 countries. Finally, in addition to other findings, the results indicated that the initial indication that the party system and the electoral system influence on electoral behavior was confirmed, or at least it is possible to affirm that, for the elections analyzed, in the 17 Latin-American countries studied, the partisan vote is explained in large part by the institutions. Since, although two institutional variables have presented the opposite direction of the expected alternative dissertation hypotheses (polarization and type of list for elections to the House of Representatives), they all presented expressive coefficients to explain the partisan vote (fragmentation, structure of competition for the Executive, and prohibition or permission for independent candidacies). That is, the answer to the research question posed is that both the party systems and electoral systems exert influence on the electoral behavior of the Latin-Americans, although it does not always point in the expected direction